Kajian hubungan antara momen dan kekuatan pada kolom bulat dari pipa baja terisi beton non pasir - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT Concrete column using steel pipe is an element of structure which retain compressive stress. This column is a new alternative in circular column design. Steel and Concrete in this structure retain force together as one structure. Steel pipe in circular column working as confinement so concrete doesn't fracture when column get a big moment.No fines concrete is a kind of concrete made of cement, aggregate and water without sand, so it has much void and lighter than ordinary concrete.This Concrete has compressive stress about 15 MPa, so it can be used to make structural column. From the two reasons above, no fines concrete column using steel pipe can be investigated. In this research 7 circular columns using steel pipe with external diameter of 112 mm are made. The concrete is made of portland cement and artifical light-weight aggregate from Cilacap with cement- aggregate ratio of 1:4, and with water-cement ratio of 0,40. Each column loaded with different excentricities of 10 mm